2011
DOI: 10.1002/rcm.4971
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for matrix effects of pesticide residue liquid chromatography/electrospray ionisation mass spectrometric determination by treatment of background mass spectra with chemometric tools

Abstract: Matrix effect (ME) - ionisation suppression or enhancement - in liquid chromatography/electrospray ionisation mass spectrometry (LC/ESI-MS) is caused by matrix components co-eluting with the analytes. ME has a complex and not fully understood nature. ME is also highly variable from sample to sample making it difficult to compensate for. In this work it was studied whether the background ion signals in scanned mass spectra of the LC effluent at the retention time of the analyte offer some insight into the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…As an alternative approach background ions could be used to correct for the matrix effect, as has been previously described for other pesticides in complicated matrices …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative approach background ions could be used to correct for the matrix effect, as has been previously described for other pesticides in complicated matrices …”
Section: Resultsmentioning
confidence: 99%
“…As an alternative approach background ions could be used to correct for the matrix effect, as has been previously described for other pesticides in complicated matrices. [27] CONCLUSIONS The aim of this study was to examine the influence of cereal type, cereal particle size and analyte concentration on the matrix effect in analysis of glyphosate. It was found that wheat and rye give very different matrix effect values in analysis of glyphosate using the glyphosate-FMOC derivative.…”
Section: Calibration Graph Slope As a Measure Of Matrix Effectmentioning
confidence: 99%
“…Matrix interference (MI%) was calculated according to following Eq. (2): where A denotes peak areas of the standard (A Standard ) and the blank matrix extract (A Post extraction spike ) spiked at the same concentration level (Kruve et al 2011). Ideally, value of 0 is related to the absence of matrix interference.…”
Section: Matrix Interference Assessmentmentioning
confidence: 99%
“…The compounds causing the matrix effect can be of different origins and have different properties. In JetStream technology, analytes eluting close to the dead time/solvent front of the LC run and non-retained hydrophilic compounds cause an ion suppression effect [20]. This effect caused a decrease in sensitivity to some metabolites and, in some cases, their loss.…”
Section: Wine Pre-treatmentmentioning
confidence: 99%